Des modèles du sujet pour éduquer à la responsabilité. Rôles de la conscience et de la méditation - Hélène Hagège (Éducation et Socialisation)
Education towards (moral) responsibility seems necessary for human future and concerns all types of education. It implies changes in subject’s functioning. Yet, implicit attitudes can hinder these changes; the subject is not fully aware of her/his thoughts and actions. Here, I thus propose answers to the following questions. What changes are to be promoted in a subject’s functioning, i.e. what are the goals of education towards responsibility? How does a subject function? And how to foster changes in a subject’s functioning patterns? In a first part, answering this first question, I give as a basis for a preliminary definition of responsibility the goal of fostering the subject’s control of her/his own functioning. In a second part, I propose a spontaneous model of the subject that explains the usual conscious experience. This model is essentially based on the “subject” word etymology, which according to me explains the common sense of subjective functioning. Then, I elaborate a model of subject that explains more accurately the subject’s functioning, based on scientific results. This leads to distinguish the notions of individual and of subject. This also reveals the usual phenomenology as being illusory. In a third part I discuss the theoretical consequences of this model with regard to education towards responsibility. Thus, the notion of control has to be replaced by the notion of regulation. Then, meditation appears as a privileged mean to operate the phenomenological change that is necessary for the subject to be conscious of her/his own functioning. This consciousness appears to be necessary to responsibility enhancement. In conclusion, I present educational perspectives and research scopes opened by these reflexions.